Concurrent FDG Avid Nasopharyngeal Lesion and Generalized Lymphadenopathy on PET-CT Imaging Is Indicative of Lymphoma in Patients with HIV Infection - Yiyan Liu (AIDS Research and Treatment)
Patients with HIV infection often have generalized lymphadenopathy and/or other lymphoid proliferation and are at significantly increased risk for lymphoma. This study retrospectively evaluated the diagnostic value of concurrent nasopharyngeal lesion and lymphadenopathy on positron emission tomography-computed tomography (PET-CT) with fluorine-18 fluorodeoxyglucose (FDG PET-CT) imaging. The eligible cases were from patients with HIV infection and lymphadenopathy and referred for FDG PET-CT to evaluate lymphoma or other malignancies prior to pathological investigation. FDG PET-CT images and interpretation reports were correlated with clinical information and pathological diagnoses. Among 22 eligible patients, FDG avid nasopharyngeal lesions were incidentally noted in 7 on PET-CT imaging, and all had lymphomas diagnosed with subsequent biopsies (6 diffuse large B-cell lymphomas and 1 Hodgkin’s lymphoma). In the remaining 15 patients with adenopathy but no visible nasopharyngeal lesion or uptake on PET-CT imaging, 9 had biopsies and lymphomas were diagnosed in 4. The patients with FDG avid retroperitoneal or intra-abdominal lymphadenopathy had a greater possibility of lymphoma, compared to those with adenopathy localized only in the upper torso. Coexistent FDG avid nasopharyngeal lesion and generalized lymphadenoapthy on PET-CT imaging are indicative of a malignant lymphoma rather than benign lymphproliferative disease or nasopharyngeal carcinoma.